The Analysis of Work Behavior and Work Result towards Work Performance - Nasution, Harmein; Marzuki, Najib Ahmad (EDUCARE, 2011)
ABSTRACT: In conducting teaching, research and community service, academic staffs should weight more on quality than quantity. In this context, individual habit reacts to the demanded jobs which are influenced by his/her knowledge, attitude, and skill. University is an organization which based on science which is not overtly competitive. The competitive advantage should lie on academic staffs as the main resource. The statement correlates with the main function of a university as the main producer of human resources which is based on science and which shows its competitive advantage. This research is to analyze the influence of work behavior and work result towards work performance. Variables for behavior are knowledge, skill, attitude, and habit. For work result, the variables are quantity, quality, and timeliness. The research is conducted in USU (Universitas Sumatera Utara or Sumatera Utara University) with 312 academic staffs as samples. Questionnaires are tested thru reliability, criteria, construction and validity tests by using factor analysis method. Then, data is analyzed thru statistical Structural Equation Method (SEM). Such methodology is chosen due to the analysis which relates to the interrelationship amongst variables, indicators, and latent variables simultaneously. The result shows that there is a significant correlation between work behavior and work result aspects where behavior aspect correlates more than that of work result aspect. KEY WORDS: Work behavior, work results, performance, teaching, research and community service, academic staffs, and competitive advantage. Â Â Â Â Â About the Authors: Dr. Ir. Harmein Nasution is a Lecturer at the Faculty of Industrial Engineering & Management USU (University of Sumatera Utara), Medan, North Sumatera, Indonesia. Prof. Dr. Najib Ahmad Marzuki is a Lecturer at the College of Arts and Sciences UUM (University of Utara Malaysia), Sintok, Kedah, Malaysia. They can be reached at: harmein_nasution@yahoo.com and najib320@uum.edu.myHow to cite this article? Nasution, Harmein & Najib Ahmad Marzuki. (2011). âThe Analysis of Work Behavior and Work Result towards Work Performanceâ in EDUCARE: International Journal for Educational Studies, Vol.3(2) February, pp.205-218. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 27, 2010); Revised (January 29, 2011); and Published (February 17, 2011).